Vietnam household survey data for cassava varietal adoption study - Le Thi Phuong Dung (International Center for Tropical Agriculture, 2017)
In 2015, CIAT and Vietnamese partners started a study on “Documenting the adoption of improved cassava varieties and assessing impacts on farm productivity and farm income of cassava genetic improvement in Vietnam”. This is the first such study in Vietnam and in the region using DNA fingerprinting to identify the cassava varieties planted by farmers and the diversity of cassava varieties collected by national institutes. The study aims to determine the best method to collect and track varietal adoption data for cassava in Vietnam, and to assess the impacts of the adoption of cassava varieties using improved methods on varietal identification. We conducted two-rounds of household survey of 949 households in 32 provinces, which represents about 95% of cassava production area in Vietnam. The data collection was implemented with the participation of five enumeration teams from partner institutions Agricultural Genetics Institute (AGI), Thai Nguyen University of Agriculture and Forestry (TNAF) and Agricultural Science for Southern Vietnam (IAS), under CIAT’s supervision. During the survey implementation, we collected both variety information reported by farmer in a survey questionnaire and planting materials for DNA extracting and fingerprinting. The DNA extraction was conducted in Vietnam by the Agricultural Genetics Institute before being sent to CIAT Headquarter in Colombia for DNA fingerprinting.